Kerjasama BNPT dan Terrorism Prevention Branch (TPB) UNODC dalam Implementasi The Agreement on Trade-Related Aspects of Intellectual Property Rights Pemerintah India dalam Melegitimasi Produksi ARV Generik Global - Muhammad Muslim; Hermini Susiatiningsih; Nadia Farabi (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
This research aims to explain the efforts of the Government of India in implementingTRIPS so as to produce generic ARV drugs under the TRIPS regime. The idea ofregulating patent protection on the health aspects of TRIPS has fueled cynical responsesfrom developing countries that view TRIPS as a form of knowledge commodification andfeudalization of information. This research is based on concerns about developingcountries access to Antiretroviral (ARV) due to price increases as a consequence of TRIPS.In response to this problem, India as the world's largest generic ARV producer has becomethe most massive state opposing patent regulation on health aspects. This research seesIndia's efforts in implementing TRIPS in order to achieve its interests through the patternof health diplomacy with the principle that health is the aspect that is interpreted ascommon goods. Periodically, India is advocating the importance of generic ARVaccessibility that is used as an antidote to the HIV / AIDS epidemic in developingcountries. Using the Critical Theory approach, India is able to encourage emancipation andsucceed in protecting the interests of developing countries with serious problems in theHIV / AIDS epidemic.